The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21660/2017.35.6722
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological Objects as Elements of Informational Life Support System and Sources of Information About the Evolution of the Environment

Abstract: ABSTRACT:The article shows the objective criteria of sacralization of objects of natural and cultural heritage of Eastern Europe and Southern Siberia, based on the performance of informational function in ancient human life-support system (as instruments of navigation in space-time). Transformation of functions of sacral objects from their inception to the beginning of the third millennium, due to the development of geo-cultural space (changes in technology, socio-cultural paradigm and social and economic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…For example, the concept of using labyrinths as sun clocks and calendars of the Stone Age reinforces the notion of the existence of a lost ancient Arctic civilization. The need for the instruments of orientation in space-time in the Arctic is consistent with the images of large ships and scenes of marine fishing depicted in rock carvings in the Republic of Karelia (on the Vyg river and White Sea islands), and in Northern Norway (Alt) (Paranina, 2011(Paranina, , 2017Paranina & Paranin, 2017a, 2017b.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…For example, the concept of using labyrinths as sun clocks and calendars of the Stone Age reinforces the notion of the existence of a lost ancient Arctic civilization. The need for the instruments of orientation in space-time in the Arctic is consistent with the images of large ships and scenes of marine fishing depicted in rock carvings in the Republic of Karelia (on the Vyg river and White Sea islands), and in Northern Norway (Alt) (Paranina, 2011(Paranina, , 2017Paranina & Paranin, 2017a, 2017b.…”
supporting
confidence: 60%
“…Geographical studies have shown that many sacred objects were originally used as the places of observation of celestial bodies for the purpose of time orientation, and also served as guidelines for movement in space. Based on that is a proposed geographical criterion of sacredness implying the acquisition and preservation of information that ensures the continuity of Life (Grigoriev, 2009;Paranina, 2011Paranina, , 2017.…”
Section: "Rossievedenie" (Russian Studies) As An Important Area Of Rementioning
confidence: 99%
“…The results of the research have been summarized by the authors in the navigation concept of information modeling of the world [5,6,7]. The concept served as the basis for further research and theoretical constructions.…”
Section: Objects and Methodsmentioning
confidence: 99%
“…Here, other easily measured indicators are also very dynamic: the length of the midday shadow, its ratio with the height of the gnomon, etc. [11]. These indicators reflect large changes in the height of the Sun by season and in the space of the region, so they have been mastered here for a long time.…”
Section: The Regions Of the Arctic Are The Most Dynamic In The Lighti...mentioning
confidence: 97%
“…На основе полевых и камеральных исследований древних и древней-ших объектов культурного наследия авторами статьи разработана рекон-струкция этапов эволюции астроно-мического ориентирования [11][12][13]. Выделенные этапы различаются по уровню освоения географического пространства, характеру инструмен-тов и степени изменения природного субстрата: ландшафтный этап (астро-номические инструменты -устойчи-вые природные объекты, технологии -прямое визирование, т.е.…”
Section: моделирование географического пространства-времени в сознаниunclassified